Rotavirus antigenemia as a common event among children hospitalised for severe, acute gastroenteritis in Belém, northern Brazil - Justino, Maria Cleonice Aguiar (2019)
Background: Rotavirus antigenemia and RNAemia (the presence of rotavirus RNA in serum) have been commonly identified among paediatric patients with acute gastroenteritis. In this study we examined the association between rotavirus antigenemia and clinical features, and sought to determine the genotypes of rotaviruses detected in paired stool and serum samples. Methods: Paired stool and serum samples were obtained from children hospitalised for acute gastroenteritis in Belém, Brazil, between June 2012 and June 2015. The 20-point Vesikari scoring system was used to assess the disease severity upon a retrospective medical record review. Stool and serum samples were primarily screened for the presence of rotavirus antigen using a commercial ELISA assay. The rotavirus isolates from stool and serum samples were genotyped by using the classical reverse-transcriptase polymerase chain reaction (RT-PCR) and/or through nucleotide sequencing of VP4 and VP7 genes. Viral load was estimated using real-time RT-PCR. Results: In total rotavirus antigen was detected in 109 (24.2%) stool samples from 451 children, whereas antigenemia occurred in 38.5% (42/109) of these patients. We demonstrated that patients positive for rotavirus RNA in paired stool and serum samples were more likely to have a higher frequency of vomiting episodes in a 24-h period (p = 0.0035). Our findings also suggested that children not vaccinated against rotavirus are more likely to develop antigenemia, as compared to those given at least one vaccine dose (p = 0.0151). G12P [8] and G2P [4] genotypes were predominant throughout the study period, accounting for 52.3% (57/109) and 27.5% (30/109) of the typed isolates, respectively. Ten stool-serum pairs could be typed for VP4 and VP7 genes. Seven of these pairs showed concordant results with G2P [4] genotype being detected in stool and serum samples, whereas discrepancies between genotypes (G2P [4]/G2P[NT] and G12P [8]/G2P[NT]) were seen in three pairs. Conclusions: Rotavirus antigenemia and RNAemia occur in a significant number of children hospitalised for acute gastroenteritis in Belém, Brazil, and may contribute to a greater disease severity, particularly translated into a greater number of vomiting episodes. This study documented a high concordance of genotypes detected in a subgroup of paired stool and serum samples